2020
DOI: 10.1021/acs.chemmater.0c03043
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Thermal Stability and Thermoelectric Properties of Yb14MnSb11 by Ce Substitution

Abstract: Yb14MnSb11 is a p-type high-temperature thermoelectric material with operational temperatures as high as 1273 K. Rare-earth (RE) substitution into this phase has been shown to increase the melting point further while also decreasing the sublimation rate. Solid solutions of 3+ RE elements with Yb2+ in Yb14MnSb11 have shown to have increased stability against oxidation. Ce is an abundant RE element, and the substitution of Ce3+ on the Yb2+ sites should increase the thermoelectric efficiency of the material due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…These two phases will be difficult to analyze by other common analytical techniques such as microprobe analysis, especially in situations when unpolished samples are examined and proper calibration standards are unavailable. A casual survey of the literature revealed multiple works that dealt with the formation of the “Yb 11 Sb 10 ” phase, in the preparation and optimization of Yb 14 MnSb 11 samples for thermoelectric studies. According to these reports, “Yb 11 Sb 10 ” was produced even with an excess of Mn, which appears to contradict the in-depth synthetic work carried out by us and described in this paper. Given the above, it is not unreasonable to expect that some of the literature may have mistakenly confused the Yb 10 MnSb 9 and Yb 11 Sb 10 phases.…”
Section: Resultsmentioning
confidence: 78%
“…These two phases will be difficult to analyze by other common analytical techniques such as microprobe analysis, especially in situations when unpolished samples are examined and proper calibration standards are unavailable. A casual survey of the literature revealed multiple works that dealt with the formation of the “Yb 11 Sb 10 ” phase, in the preparation and optimization of Yb 14 MnSb 11 samples for thermoelectric studies. According to these reports, “Yb 11 Sb 10 ” was produced even with an excess of Mn, which appears to contradict the in-depth synthetic work carried out by us and described in this paper. Given the above, it is not unreasonable to expect that some of the literature may have mistakenly confused the Yb 10 MnSb 9 and Yb 11 Sb 10 phases.…”
Section: Resultsmentioning
confidence: 78%
“…Since the crystals grow under constantly changing conditions (temperature, composition of the melt), different crystals from the same reaction or even different parts of a crystal may have inherent inhomogeneities, which result in irreproducible transport data. However, the absolute values of ρ­( T ) at room temperature for those crystals were always on the order of 1 Ω·cm, which is about 2–3 orders of magnitude higher than the corresponding values in benchmark thermoelectric materials, such as PbTe, Yb 14 MnSb 11 , and their derivatives. ,,, …”
Section: Resultsmentioning
confidence: 82%
“…However, the absolute values of ρ(T) at room temperature for those crystals were always on the order of 1 Ω•cm, which is about 2−3 orders of magnitude higher than the corresponding values in benchmark thermoelectric materials, such as PbTe, Yb 14 MnSb 11 , and their derivatives. 12,13,114,115 3.5. Magnetization.…”
Section: Resultsmentioning
confidence: 84%
“…Finding a sustainable clean energy source is an enduring issue for humankind in modern society. Despite our continuous efforts to discover and develop various energy sources, we easily overlook the fact that about 67% of the energy we use is wasted in the form of heat. , Since thermoelectric (TE) materials can directly convert wasted heat sources into electricity, these materials and devices adapting TE materials have been considered as one of the smartest solutions for energy-recycling purposes. Among the numerous candidates for this TE application, the Zintl phase is considered an excellent candidate with respect to its intrinsically semiconducting property and complex crystal structure, both of which are required for good TE candidates. In particular, the Zintl-phase A 5 M 2 Pn 6 (A = Ca, Sr, Eu, and Yb; M = Al, Ga, and In; Pn = As, Sb, and Bi) series has been extensively investigated by worldwide researchers for TE applications. Our recent studies for the Zintl-phase Ca 5– x Yb x Al 2 Sb 6 (1.0 ≤ x ≤ 5.0) system revealed that some Yb-rich compounds having a particular range of composition initially adopted the Ca 5 Al 2 Bi 6 -type phase, but they underwent a phase transition to the Ca 5 Ga 2 As 6 -type phase through the annealing process . Moreover, their electrical transport properties were also shifted from metallic to semiconducting during this phase transition.…”
Section: Introductionmentioning
confidence: 99%